Egyptian Financial Supervisory Authority (EFSA) Board of Directors Decision No. 72 of the year 2013 Dated 10/12/2013 Regarding Regulations and Controls Governing Factoring Activity = الهيئة العامة للرقابة المالية قرار مجلس الإدارة رقم 72 لسنة 2013 بتاريخ 10/12/2013 بشأن الضوابط التنظيمية والرقابية لنشاط التخصيم - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.